Climate change effects on hydrological system conditions influencing generation of storm runoff in small Alpine catchments. Issue 6 (26th January 2017) - Meißl, Gertraud; Formayer, Herbert; Klebinder, Klaus; Kerl, Florian; Schöberl, Friedrich; Geitner, Clemens; Markart, Gerhard; Leidinger, David; Bronstert, Axel
Abstract: Floods and debris flows in small Alpine torrent catchments (<10 km 2 ) arise from a combination of critical antecedent system state conditions and mostly convective precipitation events with high precipitation intensities. Thus, climate change may influence the magnitude–frequency relationship of extreme events twofold: by a modification of the occurrence probabilities of critical hydrological system conditions and by a change of event precipitation characteristics. Three small Alpine catchments in different altitudes in Western Austria (Ruggbach, Brixenbach and Längentalbach catchment) were investigated by both field experiments and process‐based simulation. Rainfall–runoff model (HQsim) runs driven by localized climate scenarios (CNRM‐RM4.5/ARPEGE, MPI‐REMO/ECHAM5 and ICTP‐RegCM3/ECHAM5) were used in order to estimate future frequencies of stormflow triggering system state conditions. According to the differing altitudes of the study catchments, two effects of climate change on the hydrological systems can be observed. On one hand, the seasonal system state conditions of medium altitude catchments are most strongly affected by air temperature‐controlled processes such as the development of the winter snow cover as well as evapotranspiration. On the other hand, the unglaciated high‐altitude catchment is less sensitive to climate change‐induced shifts regarding days with critical antecedent soil moisture and desiccated litter layer due to its elevation‐related small proportion of sensitive areas. For the period 2071–2100, the number of days with critical antecedent soil moisture content will be significantly reduced to about 60% or even less in summer in all catchments. In contrast, the number of days with dried‐out litter layers causing hydrophobic effects will increase by up to 8%–11% of the days in the two lower altitude catchments. The intensity analyses of heavy precipitation events indicate a clear increase in rain intensities of up to 10%.